Catalytic material for hydrogen production from sodium borohydride and preparation method of catalytic material
By using porous metal materials and carbon-supported trimetal catalysts in sodium borohydride hydrolysis hydrogen production catalyst, combined with pH gradient alkalization precipitation method, a nickel-cobalt-ruthenium trimetal hydroxide layer was formed, and the catalyst was solved in a high concentration of sodium borohydride solution. The structural instability and insufficient activity problems in the process have achieved efficient and stable catalytic performance and the possibility of large-scale production.
Patent Information
- Application Number
- CN202411460296.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
AI Technical Summary
The existing catalysts for hydrolysis of sodium borohydride hydrogen production have problems such as structural instability, insufficient catalytic activity and difficulty in mass production in high-concentration aqueous solutions. Especially in hot concentrated sodium borohydride solutions, the catalyst is prone to deactivate.
Using porous metal materials as mechanical support, combined with carbon-carrying trimetal catalyst, nickel, cobalt, and ruthenium trimetal particles are generated through carbonization reduction reaction of metal organic frame compounds, and nickel, cobalt, ruthenium trimetal hydroxide is loaded by pH gradient alkalization precipitation method. The material layer forms NiCoRu@C/porous metal material.
The structural stability and catalytic activity of catalytic materials in high-temperature and high-concentration sodium borohydride solution are achieved, and have excellent cycle stability and crystallization impact resistance, which is suitable for large-scale industrial production.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the fields of heterogeneous catalytic technology and new energy development technology, and in particular to a catalytic material for producing hydrogen from sodium borohydride and a preparation method thereof. Background Art
[0002] With the large-scale development and overuse of fossil fuels, environmental pollution and energy crisis problems are gradually expanding. Therefore, it is urgent to develop new energy sources that can replace fossil fuels in production and life. Hydrogen energy not only meets the requirements of green and clean, but also has the characteristics of wide sources and high energy content. It is an ideal substitute for fossil fuels. At present, common industrial hydrogen production methods include: hydrogen production from industrial by-products, hydrogen production from natural gas reforming, hydrogen production from water gas, hydrogen production from biomass, hydrogen production from water electrolysis, etc. However, the storage and transportation of hydrogen has always been a key issue restricting the development of hydrogen energy. Therefore, finding a chemical with a high active hydrogen content and matching it with a stable and efficient hydrogen production method is also one of the ways to solve the above problems.
[0003] Sodium borohydride (NaBH4) has a theoretical hydrogen storage capacity of up to 10.8%, and its physical and chemical properties are relatively stable. It is a chemical hydride with high energy density. It has a high solubility in water, and using sodium borohydride aqueous solution as a hydrogen source can achieve high energy density of hydrogen storage without danger. Hydrogen production through other high hydrogen content hydrogen sources such as ammonia borane, hydrazine hydrate, etc. will generate byproducts such as ammonia and nitrogen, while the gas product of hydrogen production through sodium borohydride is only hydrogen, which is more suitable for direct use in hydrogen-oxygen fuel cells for energy conversion. In addition, the only byproduct of hydrogen production by decomposition of sodium borohydride solution is sodium metaborate (NaBO2), which is non-toxic and recyclable. Therefore, sodium borohydride can be used as an ideal hydrogen storage material. However, the hydrogen release kinetics of sodium borohydride in alkaline aqueous solution is relatively slow. Therefore, in order to improve the hydrogen production efficiency of sodium borohydride in aqueous solution, it is necessary to develop targeted catalysts for it.
[0004] At present, most of the catalysts for hydrogen production by hydrolysis of sodium borohydride are used in dilute solution systems. Since the solubility of sodium metaborate is lower than that of sodium borohydride, the dilute solution system can avoid the precipitation of sodium metaborate, a byproduct of the reaction, but it will also directly reduce the hydrogen carrying energy density of the sodium borohydride solution, thereby reducing the practical application scope of sodium borohydride as a hydrogen storage material. Moreover, in hot and concentrated sodium borohydride solutions, the properties and mechanism of action of the catalyst are not exactly the same as those of normal temperature and dilute solutions. In addition, due to the serious exothermic reaction, in dilute solutions, a large amount of solvent can quickly take away the heat generated by the reaction, and the strong exothermic reaction and violent bubble impact in concentrated solutions make the catalyst easily disintegrate and deactivate. This poses challenging requirements for the catalyst structure. Therefore, although there are currently a large number of sodium borohydride decomposition hydrogen production catalysts, many catalysts lack structural stability and are only applicable to extremely dilute sodium borohydride solutions for stable use. For example, in the patent CN111270263A "A kind of nickel foam loaded boron-rich, oxygen-vacancy cobalt tetroxide electrode and its preparation method", a catalytic material with a nickel foam carrier and cobalt tetroxide nanowires grown on its surface as the active center was designed, and the reaction performance was tested only with 1.0 wt% NaBH4. In addition, in order to improve the activity of the catalyst, most catalysts are prepared using nanotechnology, but although they have relatively good catalytic performance (Guan SY, et al. Journal of Colloid and Interface Science, 2022, 608: 3111-3120.), because a large number of bubbles will be generated in the concentrated sodium borohydride aqueous solution, the nano-sized catalyst active components are very easy to fall off under the impact of heat release and bubbles, thereby quickly deactivating. Moreover, the nano-sized catalyst also has the problem of complex synthesis steps and difficulty in mass production.
[0005] In summary, it is of great significance to research and develop a catalyst suitable for the decomposition of high-concentration sodium borohydride aqueous solution to produce hydrogen, which has excellent catalytic activity, stable structure and is suitable for large-scale and simple production. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a catalytic material for producing hydrogen from sodium borohydride and a preparation method thereof. The catalytic material has good structural stability, excellent catalytic activity, and good cycle stability.
[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a catalytic material for producing hydrogen from sodium borohydride, which uses a porous metal material as a mechanical support and a carbon-supported trimetallic catalyst as an active component;
[0009] The carbon-supported trimetallic catalyst is generated by a metal organic framework compound through a carbonization reduction reaction, and its structure comprises a porous carbon material and trimetallic particles of nickel, cobalt and ruthenium supported on its surface.
[0010] The active components in the sodium borohydride catalytic material for producing hydrogen are located on the surface of the porous metal material.
[0011] The above-mentioned catalytic material is represented as NiCoRu@C / porous metal material, wherein the porous metal material is a mechanical support, the active component is NiCoRu@C, and NiCoRu@C represents a carbon-supported trimetallic catalyst, wherein three metal particles of nickel, cobalt and ruthenium are supported on the surface of porous carbon (C).
[0012] Preferably, the particle size of the carbon-supported trimetallic catalyst is 30-300 nm; more preferably, 30-200 nm; and in some embodiments of the present invention, it is particularly preferably 30 nm, 100 nm or 200 nm.
[0013] Preferably, in the present invention, the tri-metal particles of nickel, cobalt and ruthenium in the carbon-supported tri-metal catalyst account for 7.8%-18.4wt% of the catalytic material for producing hydrogen from sodium borohydride; more preferably, 12.4-16.1wt%.
[0014] Preferably, the porous metal material is selected from titanium mesh, nickel foam or stainless steel mesh.
[0015] The present invention also provides a method for preparing the above-mentioned catalytic material (NiCoRu@C / porous metal material), comprising the following steps:
[0016] A volatile nickel complex, a volatile cobalt complex, a volatile ruthenium complex and an imidazole compound are mixed, a metal organic framework compound is synthesized on the surface of a porous metal material by a vapor deposition method, and then the catalytic material is prepared by a carbonization reduction reaction.
[0017] The preparation method uses the orderliness and customizability of metal organic framework compounds (MOF materials) to first heat and vaporize volatile nickel complexes, volatile cobalt complexes, volatile ruthenium complexes and organic ligand imidazole compounds in an inert gas atmosphere, and then meet on the surface of the porous metal material to form MOF nuclei, which are then deposited on the surface of the carrier porous metal material for stable growth. Finally, the MOF material is carbonized and reduced under hydrogen conditions to improve the binding stability with the porous metal material, and the metal ions are reduced to metal nanoparticles to form active center sites that are tightly bound to the surface of the porous metal material of the mechanical support. Preferably, the temperature of the vapor deposition is 200°C-230°C;
[0018] Preferably, the vapor deposition time is 6-12 h;
[0019] Preferably, the temperature of the carbonization reduction is 450°C-800°C;
[0020] Preferably, the carbonization reduction time is 5-10 h.
[0021] In the above preparation method, the carbonization reduction reaction is preferably carried out using a reducing gas consisting of hydrogen and a carrier gas.
[0022] The carrier gas is preferably argon or nitrogen.
[0023] The volume ratio of hydrogen to carrier gas is preferably 1: (10~100).
[0024] The mass ratio of the flow rate of the reducing gas to the volatile nickel complex (preferably nickel acetylacetonate) is 30-3000 ccm / g.
[0025] In the above-mentioned method for preparing the catalytic material, preferably, the volatile nickel complex is selected from one or more of nickel acetylacetonate, nickelocene or nickel acetate; more preferably nickel acetylacetonate.
[0026] Preferably, the volatile cobalt complex is selected from one or more of cobalt acetylacetonate, cobaltocene or cobalt acetate; more preferably, cobalt acetylacetonate.
[0027] Preferably, the volatile ruthenium complex is selected from one or more of ruthenium acetylacetonate or ruthenocene; more preferably, ruthenium acetylacetonate.
[0028] Further preferably, the volatile nickel complex is selected from nickel acetylacetonate, the volatile cobalt complex is selected from cobalt acetylacetonate, and the volatile ruthenium complex is selected from ruthenium acetylacetonate.
[0029] More preferably, the mass ratio of nickel acetylacetonate, cobalt acetylacetonate and ruthenium acetylacetonate is (6-15):(6-15):1.
[0030] In the above preparation method, the imidazole compound includes but is not limited to 2-methylimidazole, benzimidazole, trimesic acid, 2-nitroimidazole, etc. In some specific embodiments of the present invention, 2-methylimidazole is preferred.
[0031] In the above-mentioned NiCoRu@C / porous metal material preparation method, the mass ratio of nickel acetylacetonate to 2-methylimidazole is (2-3):5.
[0032] Preferably, in the present invention, the catalytic material further comprises a nickel-cobalt-ruthenium trimetal hydroxide layer, and the nickel-cobalt-ruthenium trimetal hydroxide layer is loaded on the surface of the above-mentioned catalytic material (NiCoRu@C / porous metal material).
[0033] Preferably, the particle size of the nickel-cobalt-ruthenium trimetallic hydroxide layer is 20-400 nm;
[0034] Preferably, the thickness of the nickel-cobalt-ruthenium trimetallic hydroxide layer is 200-500 nm.
[0035] The present invention also provides application of the above-mentioned catalytic material in producing hydrogen from sodium borohydride.
[0036] The above-mentioned catalytic material has a stable structure in the production of hydrogen from hot concentrated sodium borohydride, and has excellent catalytic activity and cycle stability. The present invention also provides a method for preparing the above-mentioned catalytic material for hydrogen production from sodium borohydride, comprising the following steps:
[0037] 1) The above-mentioned sodium borohydride catalytic material for hydrogen production (NiCoRu@C / porous metal material) is immersed in an aqueous solution containing a nickel inorganic salt and a cobalt inorganic salt, and a base is added under heating conditions to control the pH to two gradients of 7-8 and 10-12 in turn to obtain a reaction system S1;
[0038] 2) The reaction system S1 and the ruthenium inorganic salt are mixed and heated to react to obtain the catalytic material.
[0039] The preparation method loads the hydroxide containing nickel, cobalt and ruthenium trimetallics on the surface of the NiCoRu@C / porous metal material through a pH gradient alkalinization precipitation method, thereby significantly improving the catalytic activity and structural stability of the material.
[0040] Among them, the pH gradient alkalinization precipitation method is to adjust the acidity and alkalinity of the solution with a certain gradient, wherein the adjusted alkaline substances can be of the same type or different types, aiming to make the species in the solution undergo nucleation precipitation process at a relatively slow and adjustable speed.
[0041] The above method adjusts the pH to 7-8, so that the two metal ions of nickel and cobalt are converted into hydroxide crystal nuclei containing nickel and cobalt; then the pH of the system is adjusted to 10-12 to promote the further growth of the hydroxide particles containing nickel and cobalt, thereby forming a sheet structure. Then, the ruthenium inorganic salt is mixed with the reaction system S1 and heated, with the purpose of adsorbing and enriching the ruthenium ions on the surface of the hydroxide precipitate containing nickel and cobalt by ion replacement. If the pH is directly adjusted to 10-12, the catalytic material in the solution will have different growth stages, resulting in poor particle uniformity of the final catalytic material.
[0042] The above method uses pH gradient deposition and ruthenium enrichment to uniformly distribute the three metals of nickel, cobalt and ruthenium as active centers on the surface of porous carbon without significantly changing the morphology of the catalytic material, thereby generating the carbon-supported trimetallic catalyst. In addition, the introduction of ruthenium as a noble metal enables the carbon-supported trimetallic catalyst to obtain more fully exposed active sites, thereby further improving the catalytic activity and cycle stability of the catalytic material for hydrogen production from sodium borohydride described in the present invention. Preferably, the mass ratio of the catalytic material for hydrogen production from sodium borohydride described in any one of claims 1 to 4, the nickel inorganic salt and the cobalt inorganic salt is 1: (0.06-6): (0.06-6);
[0043] The molar ratio of nickel element to cobalt element in the nickel inorganic salt and the cobalt inorganic salt is (0.1-10):1;
[0044] The molar ratio of nickel to ruthenium elements in the nickel inorganic salt and the ruthenium inorganic salt is 2:(0.3-0.9).
[0045] In the above preparation method, the nickel inorganic salt includes but is not limited to hydrated nickel chloride, nickel nitrate, nickel sulfate and the like.
[0046] The inorganic cobalt salt includes but is not limited to hydrated cobalt chloride, cobalt nitrate, cobalt sulfate and the like.
[0047] The ruthenium inorganic salt includes but is not limited to hydrated ruthenium chloride, ruthenium nitrate, ruthenium sulfate and the like.
[0048] In some specific embodiments of the present invention, the nickel inorganic salt is preferably hydrated nickel chloride, the cobalt inorganic salt is preferably hydrated cobalt chloride, and the ruthenium inorganic salt is preferably hydrated ruthenium chloride.
[0049] More preferably, the concentration of the hydrated nickel chloride is 0.01-1.0 M.
[0050] Further preferably, the molar ratio of the hydrated ruthenium chloride to the hydrated nickel chloride is (0.1-0.3):1.
[0051] In the above preparation method, the base in step 1) is divided into two types:
[0052] One is a substance used to adjust the pH to 7-8, which is selected from saturated sodium carbonate aqueous solution, sodium phosphate solution or ammonia water; the other is a substance used to adjust the pH to 10-12, which is selected from 0.5-1.5 M sodium hydroxide solution.
[0053] Preferably, the heating temperature in step 1) is 40°C-55°C;
[0054] Preferably, the heating temperature in step 2) is 65°C-80°C.
[0055] Preferably, the heating time in step 2) is 0.5-3 h.
[0056] After the above step 2) is completed, post-processing such as washing and drying is also included.
[0057] The present invention has no particular limitation on the washing solvent and drying method, which are solvents or methods well known to those skilled in the art.
[0058] The washing is preferably water washing.
[0059] The drying temperature is preferably 50°C-80°C.
[0060] The present invention also provides a method for producing hydrogen from sodium borohydride, which uses the above-mentioned catalytic material (NiCoRu@C / porous metal material) or the above-mentioned catalytic material (catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer) to catalyze sodium borohydride to prepare hydrogen.
[0061] The catalytic material of the present invention makes the production of hydrogen from sodium borohydride have excellent catalytic activity, the catalytic material has good structural stability, good tolerance to reaction high temperature and bubble impact, and good resistance to crystallization impact. When the catalytic material is applied to the production of hydrogen from a hot alkaline concentrated sodium borohydride aqueous solution, it will not be affected by the sodium metaborate generated by the side reaction in the concentrated sodium borohydride solution, and after multiple cycles of reaction, the catalytic active center can still be ensured not to be lost, and the overall structure of the catalytic material remains basically intact without a large amount of breakage.
[0062] In addition, the catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer increases the exposure area of the high-activity component by using a pH gradient alkalinization precipitation method on the NiCoRu@C / porous metal material catalytic material, thereby further improving the catalytic activity and cycle stability of the material.
[0063] Compared with the prior art, the catalytic material for hydrogen production from sodium borohydride provided by the present invention uses a porous metal material as a mechanical support and a carbon-supported trimetallic catalyst as an active ingredient; the carbon-supported trimetallic catalyst is generated by a metal organic framework compound through a carbonization reduction reaction, and its structure comprises a porous carbon material and trimetallic particles of nickel, cobalt and ruthenium loaded on its surface. The catalytic material has high catalytic activity, good cycle stability, structural stability, crystallization impact resistance and high air permeability. The catalytic material obtained by loading a nickel, cobalt and ruthenium trimetallic hydroxide layer on the surface of the catalytic material by a pH gradient alkalinization precipitation method has better catalytic activity, structural stability and cycle stability. In addition, the synthesis method of the catalytic material of the present invention is simple, suitable for large-scale industrial production, and provides a new idea for hydrogen production from hot alkaline concentrated sodium borohydride aqueous solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1This is a test graph of the catalytic performance of the catalytic material prepared in Example 1 in a 25 wt% sodium borohydride aqueous solution;
[0065] Figure 2 This is a test diagram of the catalytic material cycle performance prepared in Example 1;
[0066] Figure 3 A comparison chart of the catalytic performance of the catalytic materials prepared in Examples 1-8;
[0067] Figure 4 A comparison chart of the catalytic performance of the catalytic materials prepared in Example 1 and Examples 9-15;
[0068] Figure 5 The catalytic performance comparison diagram of the catalytic materials prepared in Example 1 and Comparative Examples 1-3;
[0069] Figure 6 are scanning electron microscope images, wherein (a) is nickel foam, (b) is the catalytic material prepared in Example 2, (c) is the catalytic material prepared in Example 3, (d) is the catalytic material prepared in Example 6, (e) is the catalytic material prepared in Example 10, and (f) is the catalytic material prepared in Example 15;
[0070] Figure 7 The scanning electron microscope image of the catalytic material prepared in Example 1 and the elemental analysis diagram of C, Ni, Co and Ru elements in the catalytic material. DETAILED DESCRIPTION
[0071] In order to further illustrate the present invention, the catalytic material for producing hydrogen from sodium borohydride and the preparation method thereof provided by the present invention are described in detail below in conjunction with examples.
[0072] Example 1
[0073] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.397 g of 2-methylimidazole were placed at the front end of a tube furnace. The position of 2-methylimidazole was closer to the center of the tube furnace than the position of the trimetallic salt. A titanium mesh with a diameter of 4 cm was placed in the middle of the tube furnace. Then, the tube furnace was heated to 215°C and kept warm in an argon flow (2000 ccm) for 8 h. After that, the temperature of the tube furnace was raised to 500°C, and a hydrogen flow (100 ccm) was added to the argon flow. After keeping warm for 7 h, the temperature was cooled to room temperature to obtain a catalytic material for hydrogen production from sodium borohydride, wherein the trimetallic particles of nickel, cobalt and ruthenium accounted for 12.4wt% of the catalytic material for hydrogen production from sodium borohydride.
[0074] Example 2
[0075] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.397 g of 2-methylimidazole are placed at the front end of a tube furnace. The position of 2-methylimidazole is closer to the center of the tube furnace than the position of the trimetallic salt. A piece of nickel foam with a diameter of 4 cm is placed in the middle of the tube furnace. Then, the tube furnace is heated to 215°C and kept warm in an argon flow (2000 ccm) for 8 h. After that, the temperature of the tube furnace is raised to 500°C, and a hydrogen flow (100 ccm) is added to the argon flow. After keeping warm for 7 h, the temperature is cooled to room temperature to obtain a catalytic material for hydrogen production from sodium borohydride, wherein the trimetallic particles of nickel, cobalt and ruthenium account for 16.1 wt% of the catalytic material for hydrogen production from sodium borohydride, and the particle size of the carbon-supported trimetallic catalyst is 30 nm.
[0076] Example 3
[0077] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.016 g of ruthenium acetylacetonate and 0.595 g of 2-methylimidazole were placed at the front end of a tube furnace. The position of 2-methylimidazole was closer to the center of the tube furnace than the position of the trimetallic salt. A titanium mesh with a diameter of 4 cm was placed in the middle of the tube furnace. Then, the tube furnace was heated to 215°C and kept warm in an argon flow (2000 ccm) for 8 h. After that, the temperature of the tube furnace was raised to 500°C, and a hydrogen flow (100 ccm) was added to the argon flow. After keeping warm for 7 h, the temperature was cooled to room temperature to obtain a catalytic material for hydrogen production from sodium borohydride, wherein the trimetallic particles of nickel, cobalt and ruthenium accounted for 13.4wt% of the catalytic material for hydrogen production from sodium borohydride, and the particle size of the carbon-supported trimetallic catalyst was 100 nm.
[0078] Example 4
[0079] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.040 g of ruthenium acetylacetonate and 0.397 g of 2-methylimidazole are placed at the front end of a tube furnace. The position of 2-methylimidazole is closer to the center of the tube furnace than the position of the trimetallic salt. A titanium mesh with a diameter of 4 cm is placed in the middle of the tube furnace. Then, the tube furnace is heated to 215°C and kept warm for 8 hours in an argon flow (2000 ccm). After that, the temperature of the tube furnace is raised to 500°C, and a hydrogen flow (100 ccm) is added to the argon flow. After keeping warm for 7 hours, it is cooled to room temperature to obtain a catalytic material for hydrogen production from sodium borohydride. Among them, the trimetallic particles of nickel, cobalt and ruthenium account for 12.4-16.1wt% of the catalytic material for hydrogen production from sodium borohydride. Among them, the trimetallic particles of nickel, cobalt and ruthenium account for 14.2wt% of the catalytic material for hydrogen production from sodium borohydride.
[0080] Example 5
[0081] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.397 g of 2-methylimidazole were placed at the front end of a tube furnace, and the position of 2-methylimidazole was closer to the center of the tube furnace than the position of the trimetallic salt. A titanium mesh with a diameter of 4 cm was placed in the middle of the tube furnace. Then, the tube furnace was heated to 200°C and kept warm in an argon flow (2000 ccm) for 6 h. After that, the temperature of the tube furnace was raised to 450°C, and a hydrogen flow (100 ccm) was added to the argon flow. After keeping warm for 5 h, it was cooled to room temperature to obtain a catalytic material for hydrogen production from sodium borohydride. Among them, the trimetallic particles of nickel, cobalt and ruthenium accounted for 13.8wt% of the catalytic material for hydrogen production from sodium borohydride.
[0082] Example 6
[0083] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.397 g of 2-methylimidazole are placed at the front end of a tube furnace. The position of 2-methylimidazole is closer to the center of the tube furnace than the position of the trimetallic salt. A titanium mesh with a diameter of 4 cm is placed in the middle of the tube furnace. Then, the tube furnace is heated to 230°C and kept warm in an argon flow (2000 ccm) for 12 h. After that, the temperature of the tube furnace is raised to 800°C, and a hydrogen flow (100 ccm) is added to the argon flow. After keeping warm for 10 h, the temperature is cooled to room temperature to obtain a catalytic material for hydrogen production from sodium borohydride, wherein the trimetallic particles of nickel, cobalt and ruthenium account for 15.2wt% of the catalytic material for hydrogen production from sodium borohydride, and the particle size of the carbon-supported trimetallic catalyst is 200 nm.
[0084] Example 7
[0085] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.397 g of 2-methylimidazole were placed at the front end of a tube furnace. The position of 2-methylimidazole was closer to the center of the tube furnace than the position of the trimetallic salt. A titanium mesh with a diameter of 4 cm was placed in the middle of the tube furnace. Then, the tube furnace was heated to 215°C and kept warm in an argon flow (2800 ccm) for 8 h. After that, the temperature of the tube furnace was raised to 500°C, and a hydrogen flow (28 ccm) was added to the argon flow. After keeping warm for 7 h, the temperature was cooled to room temperature to obtain a catalytic material for hydrogen production from sodium borohydride, wherein the trimetallic particles of nickel, cobalt and ruthenium accounted for 14.8wt% of the catalytic material for hydrogen production from sodium borohydride.
[0086] Example 8
[0087] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.397 g of 2-methylimidazole were placed at the front end of a tube furnace. The position of 2-methylimidazole was closer to the center of the tube furnace than the position of the trimetallic salt. A titanium mesh with a diameter of 4 cm was placed in the middle of the tube furnace. Then, the tube furnace was heated to 215°C and kept warm in an argon flow (28 ccm) for 8 h. After that, the temperature of the tube furnace was raised to 500°C, and a hydrogen flow (2.8 ccm) was added to the argon flow. After keeping warm for 7 h, the temperature was cooled to room temperature to obtain a catalytic material for hydrogen production from sodium borohydride, wherein the trimetallic particles of nickel, cobalt and ruthenium accounted for 15.3wt% of the catalytic material for hydrogen production from sodium borohydride.
[0088] Figure 6 are scanning electron microscope images, where (b) is the catalytic material prepared in Example 2, (c) is the catalytic material prepared in Example 3, and (d) is the catalytic material prepared in Example 6, indicating that Examples 1-8 successfully prepared NiCoRu@C / porous metal materials, in which the porous metal material is used as a mechanical support and the carbon-supported trimetallic catalyst NiCoRu@C is used as an active ingredient. NiCoRu@C represents a carbon-supported trimetallic catalyst, in which three metal particles of nickel, cobalt and ruthenium are loaded on the surface of the porous carbon (C).
[0089] Example 9
[0090] A gradient alkalization method was performed on the basis of the sodium borohydride catalytic material for hydrogen production prepared in Example 1. 0.8 g of the sodium borohydride catalytic material for hydrogen production was used as a precursor and immersed in 20 mL of an aqueous solution containing 0.64 g of nickel chloride hexahydrate and 0.64 g of cobalt chloride hexahydrate. A saturated sodium carbonate aqueous solution was slowly added under stirring and heating at 50°C. After adjusting the pH to 7, 1.0 M sodium hydroxide was slowly added to adjust the pH to 10. After that, 0.14 g of ruthenium chloride trihydrate was added in an oil bath at 70°C and stirred for 2 h. Finally, the mixture was washed three times with deionized water and vacuum dried to obtain a catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer.
[0091] Example 10
[0092] A gradient alkalization method was performed on the basis of the sodium borohydride catalytic material for hydrogen production prepared in Example 1. 0.8 g of the sodium borohydride catalytic material for hydrogen production was used as a precursor and immersed in 20 mL of an aqueous solution containing 0.048 g of nickel chloride hexahydrate and 0.048 g of cobalt chloride hexahydrate. A saturated sodium carbonate aqueous solution was slowly added under stirring and heating at 50°C. After adjusting the pH to 7, 1.0 M sodium hydroxide was slowly added to adjust the pH to 10. After that, 0.005 g of ruthenium chloride trihydrate was added in an oil bath at 70°C and stirred for 2 h. Finally, the mixture was washed three times with deionized water and vacuum dried to obtain a catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer.
[0093] Embodiment 11
[0094] A gradient alkalization method was performed on the basis of the sodium borohydride catalytic material for hydrogen production prepared in Example 1. 0.8 g of the sodium borohydride catalytic material for hydrogen production was used as a precursor and immersed in 20 mL of an aqueous solution containing 4.8 g of nickel chloride hexahydrate and 4.8 g of cobalt chloride hexahydrate. A saturated sodium carbonate aqueous solution was slowly added under stirring and heating at 50°C. After adjusting the pH to 7, 1.0 M sodium hydroxide was slowly added to adjust the pH to 10. After that, 1.58 g of ruthenium chloride trihydrate was added in an oil bath at 70°C and stirred for 2 h. Finally, the mixture was washed three times with deionized water and dried in a vacuum to obtain a catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer.
[0095] Example 12
[0096] A gradient alkalization method was performed on the basis of the sodium borohydride catalytic material for hydrogen production prepared in Example 1. 0.8 g of the sodium borohydride catalytic material for hydrogen production was used as a precursor and immersed in 20 mL of an aqueous solution containing 0.64 g of nickel chloride hexahydrate and 0.64 g of cobalt chloride hexahydrate. A saturated sodium carbonate aqueous solution was slowly added under stirring and heating at 40°C. After adjusting the pH to 7, 1.0 M sodium hydroxide was slowly added to adjust the pH to 10. After that, 0.14 g of ruthenium chloride trihydrate was added in an oil bath at 65°C and stirred for 0.5 h. Finally, the mixture was washed three times with deionized water and vacuum dried to obtain a catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer.
[0097] Embodiment 13
[0098] A gradient alkalization method was performed on the basis of the sodium borohydride catalytic material for hydrogen production prepared in Example 1. 0.8 g of the sodium borohydride catalytic material for hydrogen production was used as a precursor and immersed in 20 mL of an aqueous solution containing 0.64 g of nickel chloride hexahydrate and 0.64 g of cobalt chloride hexahydrate. A saturated sodium carbonate aqueous solution was slowly added under stirring and heating at 55°C. After adjusting the pH to 7, 1.0 M sodium hydroxide was slowly added to adjust the pH to 10. After that, 0.14 g of ruthenium chloride trihydrate was added in an oil bath at 80°C and stirred for 3 h. Finally, the mixture was washed three times with deionized water and vacuum dried to obtain a catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer.
[0099] Embodiment 14
[0100] A gradient alkalization method was performed on the basis of the sodium borohydride catalytic material for hydrogen production prepared in Example 1. 0.8 g of the sodium borohydride catalytic material for hydrogen production was used as a precursor and immersed in 20 mL of an aqueous solution containing 0.64 g of nickel chloride hexahydrate and 0.64 g of cobalt chloride hexahydrate. A saturated sodium carbonate aqueous solution was slowly added under stirring and heating at 50°C. After adjusting the pH to 7, 0.5 M sodium hydroxide was slowly added to adjust the pH to 10. After that, 0.14 g of ruthenium chloride trihydrate was added in an oil bath at 70°C and stirred for 2 h. Finally, the mixture was washed three times with deionized water and dried in a vacuum to obtain a catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer.
[0101] Embodiment 15
[0102] A gradient alkalization method was performed on the basis of the sodium borohydride catalytic material for hydrogen production prepared in Example 1. 0.8 g of the sodium borohydride catalytic material for hydrogen production was used as a precursor and immersed in 20 mL of an aqueous solution containing 0.64 g of nickel chloride hexahydrate and 0.64 g of cobalt chloride hexahydrate. A saturated sodium carbonate aqueous solution was slowly added under stirring and heating at 50°C. After adjusting the pH to 8, 1.5 M sodium hydroxide was slowly added to adjust the pH to 12. After that, 0.14 g of ruthenium chloride trihydrate was added in an oil bath at 70°C and stirred for 2 h. Finally, the mixture was washed three times with deionized water and dried in a vacuum to obtain a catalytic material containing a nickel-cobalt-ruthenium trimetallic hydroxide layer.
[0103] Figure 6 (e) is the catalytic material prepared in Example 10, and (f) is the catalytic material prepared in Example 15, indicating that Examples 9-15 successfully prepared catalytic materials containing a nickel-cobalt-ruthenium trimetal hydroxide layer, wherein the nickel-cobalt-ruthenium trimetal hydroxide layer is loaded on the surface of the catalytic material NiCoRu@C / porous metal material.
[0104] Comparative Example 1
[0105] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.47 g of 2-methylimidazole were placed at the front end of the tube furnace. The position of 2-methylimidazole was closer to the center of the tube furnace than the trimetallic salt. A titanium mesh with a diameter of 4 cm was placed in the middle of the tube furnace. Then, the tube furnace was heated to 200°C and kept warm for 8 h in an argon flow (50 ccm). After that, the temperature was kept constant, and a hydrogen flow (50 ccm) was added to the argon flow and kept warm for 8 h.
[0106] Comparative Example 2
[0107] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.47 g of 2-methylimidazole were placed at the front end of the tube furnace. The position of 2-methylimidazole was closer to the center of the tube furnace than the trimetallic salt. A titanium mesh with a diameter of 4 cm was placed in the middle of the tube furnace. Then, the tube furnace was heated to 200°C and kept warm for 8 h in an argon flow (50 ccm). After that, the temperature of the tube furnace was raised to 500°C, and only carbonization operation was performed without hydrogen reduction, and the temperature was kept warm for 8 h.
[0108] Comparative Example 3
[0109] 0.238 g of nickel acetylacetonate, 0.238 g of cobalt acetylacetonate, 0.024 g of ruthenium acetylacetonate and 0.47 g of 2-methylimidazole were placed at the front end of the tube furnace. The position of 2-methylimidazole was closer to the center of the tube furnace than the trimetallic salt. A titanium mesh with a diameter of 4 cm was placed in the middle of the tube furnace. Then, the tube furnace was heated to 200°C and kept warm for 4 h in an argon flow (50 ccm). After that, the temperature of the tube furnace was raised to 500°C, and a hydrogen flow (50 ccm) was added to the argon flow, and the temperature was kept warm for 4 h.
[0110] Performance Test:
[0111] 1. Catalytic performance test
[0112] The catalytic material performance test methods of the above Examples 1-15 and Comparative Examples 1-3 are the same, and the reaction system is: 5 g of sodium borohydride and 0.5 g of sodium hydroxide are dissolved in 20 mL of deionized water. While maintaining the system temperature at 80°C, a 1.5 cm diameter catalytic material disc (cut out from the center of the catalytic material prepared in each Example and Comparative Example) is added, and the hydrogen production is determined by the water displacement method.
[0113] By comparing Comparative Examples 1-3 and Examples 1-8, the results show that the sodium borohydride hydrogen production catalytic material prepared by first using vapor deposition to prepare MOF material and then carbonizing and reducing to prepare nickel, cobalt, and ruthenium trimetallic hydrogen production catalytic material as the catalytic active center has excellent catalytic activity and stability, and the preparation method of the catalytic material is suitable for large-scale preparation. In addition, after the catalytic material prepared in Example 1 is treated by pH gradient alkalinization precipitation method, the catalytic performance of the catalytic material is further improved.
[0114] (II) Cyclic stability performance test
[0115] The catalytic performance of the catalytic material prepared in Example 1 was tested by multiple cycles using the above-mentioned reaction system for catalytic performance testing. Figure 2 As shown, the results indicate that the catalytic activity of the catalytic material remains stable after 10 cycle tests, and the hydrogen production rate is higher than 4 L / (g•min).
[0116] In addition to the above Figure 6 and Figure 2 , the present invention Figure 1 This is a test graph of the catalytic performance of the catalytic material prepared in Example 1 in a 25 wt% sodium borohydride aqueous solution; Figure 3 A comparison chart of the catalytic performance of the catalytic materials prepared in Examples 1-8; Figure 4 A comparison chart of the catalytic performance of the catalytic materials prepared in Example 1 and Examples 9-15; Figure 5 The catalytic performance comparison diagram of the catalytic materials prepared in Example 1 and Comparative Examples 1-3; Figure 7 The scanning electron microscope image of the catalytic material prepared in Example 1 and the elemental analysis diagram of C, Ni, Co, and Ru in the catalytic material. The description of the above embodiments is only used to help understand the method of the present invention and its core concept. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A catalytic material for producing hydrogen from sodium borohydride, characterized in that: The porous metal material is used as a mechanical support and the carbon-supported trimetallic catalyst is used as an active component; The carbon-supported trimetallic catalyst is generated by a metal organic framework compound through a carbonization reduction reaction, and its structure comprises a porous carbon material and trimetallic particles of nickel, cobalt and ruthenium supported on its surface.
2. The catalytic material for producing hydrogen from sodium borohydride according to claim 1, characterized in that: The particle size of the carbon-supported trimetallic catalyst is 30-300 nm.
3. The catalytic material for producing hydrogen from sodium borohydride according to claim 1, characterized in that: The tri-metal particles of nickel, cobalt and ruthenium in the carbon-supported tri-metal catalyst account for 7.8%-18.4wt% of the catalytic material for producing hydrogen from sodium borohydride.
4. The catalytic material for producing hydrogen from sodium borohydride according to claim 1, characterized in that: The porous metal material is selected from titanium mesh, nickel foam or stainless steel mesh.
5. The catalytic material for producing hydrogen from sodium borohydride according to any one of claims 1 to 4, characterized in that: The catalytic material further comprises a nickel-cobalt-ruthenium trimetal hydroxide layer, and the nickel-cobalt-ruthenium trimetal hydroxide layer is loaded on the surface of the catalytic material according to any one of claims 1-4.
6. The catalytic material for producing hydrogen from sodium borohydride according to claim 5, characterized in that: The particle size of the nickel-cobalt-ruthenium trimetallic hydroxide layer is 20-400 nm; The thickness of the nickel-cobalt-ruthenium trimetallic hydroxide layer is 200-500 nm.
7. Use of the catalytic material according to any one of claims 1 to 6 in producing hydrogen from sodium borohydride.
8. The method for preparing the catalytic material for producing hydrogen from sodium borohydride according to any one of claims 1 to 4, characterized in that: The following steps are involved: A volatile nickel complex, a volatile cobalt complex, a volatile ruthenium complex and an imidazole compound are mixed, a metal organic framework compound is synthesized on the surface of a porous metal material by a vapor deposition method, and then the catalytic material is prepared by a carbonization reduction reaction.
9. The preparation method according to claim 8, characterized in that: The temperature of the vapor deposition is 200°C-230°C; The vapor deposition time is 6-12 h; The carbonization temperature is 450°C-800°C; The carbonization time is 5-10 h.
10. The method for preparing the catalytic material for producing hydrogen from sodium borohydride according to claim 5 or 6, characterized in that: The following steps are involved: 1) immersing the sodium borohydride catalytic material for hydrogen production according to any one of claims 1 to 4 in an aqueous solution containing a nickel inorganic salt and a cobalt inorganic salt, and controlling the pH to two gradients of 7-8 and 10-12 by adding a base under heating conditions to obtain a reaction system S1; 2) mixing the reaction system S1 and the ruthenium inorganic salt and heating them to obtain the catalytic material according to claim 5 or 6; Wherein, the mass ratio of the sodium borohydride catalytic material for hydrogen production according to any one of claims 1 to 4, the nickel inorganic salt and the cobalt inorganic salt is 1: (0.06-6): (0.06-6); The molar ratio of nickel element to cobalt element in the nickel inorganic salt and the cobalt inorganic salt is (0.1-10):1; The molar ratio of nickel to ruthenium elements in the nickel inorganic salt and the ruthenium inorganic salt is 2:(0.3-0.9).